Pastophoria and Altars: Interaction in Ethiopian Liturgy and Church Architecture - Fritsch, Emmanuel; Gervers, Michael (Aethiopica, 2007)
FOR THE PHOTOGRAPHS BELONGING TO THE ARTICLE SEE SUPPLEMENTARY FILES > There are three parts to the interior space of ancient Ethiopian churches: a sanctuary (Mäqdäs) which is expanded into the “Holy Place” (Qǝddǝst) and the place of the assembly (Qǝne maḥlet). Four rooms stand at the corners of a cross-in-square interior: two service rooms on either side of a narthex-like entrance-room, westwards and, more important for the present discussion, two eastern service rooms which flank the sanctuary. These are called the pastophoria. After early input from Syria-Palestine, the Ethiopian basilicas took on an Aksumite character. Their development continued in a loose relationship with changes on the Egyptian scene, notably with a double phenomenon: the evolution of the rite and place of preparation of the bread and wine for Mass (the prothesis), and the demand for more altars at a time when churches could not be multiplied in Egypt. A study of architectural changes in the churches, alongside a comparison of liturgical practices and clues found in iconography and Coptic and Syriac literature, can bear witness to how the liturgy of the Ethiopian Church developed. Such investigation is all the more important because the absence of written documentation until the 13th century has left the church buildings as almost the only evidence available for study. The present study concentrates on the evolution and eventual disappearance of the pastophoria. The nature and location of the altars provides further evidence for dating. It should be noted that Ethiopia does not entirely abide by the Coptic models, essentially because what provoked change in Egypt did not exist in Ethiopia. Many questions still remain to be answered, including: When and where did the large monolithic altar of the permanent Coptic altar type first appear? Why are the West-Syriac and Ethiopian Churches today the only ones to celebrate Mass in a synchronized manner? We hope to address these and other questions at a later date.